Komposisi dan Proporsi Antropometri Fasad Arsitektur Tradisional Banua Oge - Nurhalisa, Siti (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, 2024)
Architecture should have positive value, and create meaning as objects, culture, concepts, patterns and forms of interpretation and symbols of expression contained in human thought in response to architecture. A building, especially a building with a traditional concept, must reflect its identity as a product of vernacular architecture. With this, traditional architecture is a human effort to create an environment in the form of shelter to fulfill needs by considering traditional aspects and rituals passed down by previous generations. Proportions in the traditional architectural works of the archipelago are the basis of design, which is fundamental in building traditional architectural works. raditional architecture basically does not have a standard measuring tool (meters / feet) as a reference, at that time people used intuition based on culture and beliefs in building. For example, the application of human body anthropometry as a measuring tool. The size of the human body as a measuring tool is related to cosmological values, where traditional architecture believes that humans are a microcosm and a reflection of the macrocosm of the universe. The universe is believed to be divided into three parts, namely the upper realm, middle realm and lower realm. This is represented in the human body which is divided into the head (top), body (middle) and legs (bottom). These cosmological values are closely related to the application of traditional architecture, as the house is a reflection of humans and the universe. So that the proportions in traditional archipelago architecture are closely related to anthropometric theory as a measuring tool.